2019
DOI: 10.1097/iae.0000000000002090
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Choroidal and Retinal Thicknesses in Children With Myopic Shift

Abstract: Choroidal thinning occurs early in myopic progression. Axial length increase and choroidal thinning are independently associated with myopic shift.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 22 publications
(24 reference statements)
6
73
1
Order By: Relevance
“…Interestingly, this study also found a significant relationship between the baseline choroidal thickness and the rate of eye growth, with a thicker choroid at baseline being associated with a slower rate of axial eye growth. More recently, a significant thinning of the choroid over time (mean change of 11 μm) was also reported over a 12‐month period, in 88 Chinese school children with a documented myopic shift in refraction of > 0.50 D . This population at baseline included myopic, emmetropic and hyperopic children, indicating that choroidal thinning is a feature observed in myopia progression, as well as in emmetropic children who are developing myopia.…”
Section: Choroidal Changes In Myopiamentioning
confidence: 69%
“…Interestingly, this study also found a significant relationship between the baseline choroidal thickness and the rate of eye growth, with a thicker choroid at baseline being associated with a slower rate of axial eye growth. More recently, a significant thinning of the choroid over time (mean change of 11 μm) was also reported over a 12‐month period, in 88 Chinese school children with a documented myopic shift in refraction of > 0.50 D . This population at baseline included myopic, emmetropic and hyperopic children, indicating that choroidal thinning is a feature observed in myopia progression, as well as in emmetropic children who are developing myopia.…”
Section: Choroidal Changes In Myopiamentioning
confidence: 69%
“…22 The thinning of the choroid is noted early in myopic progression, and increases in AL and choroidal thinning are associated independently with myopic shift. 23 A study that evaluated the progression pattern of disc and retinal lesions in highly myopic adolescents found that progressive worsening of myopia and early-onset fundus tessellation were associated with thinner choroid. 24 Therefore, it is important to explore the associations between tilted optic discs and ChT in young myopic patients.…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, a 1-year follow-up study of 118 Chinese children aged 7 to 12 years found choroidal thinning in eyes with a myopic shift in refraction, but not in eyes without such shift. 22 Consequently, the choroid appears to thicken in normallydeveloping young eyes and thin in eyes that have myopia. Our finding of a decreased thickening of the choroid in eyes that had a negative refractive development supports this association.…”
Section: Discussionmentioning
confidence: 99%
“…1,[17][18][19][20] Given this complexity, it is obvious that prospective studies are particularly valuable. [21][22][23] Previous longitudinal studies have been relatively small and mainly investigated populations with high myopia rates. 21,22 We describe changes in choroidal thickness from the age of 11 to 16 years in a prospective cohort study, and its association with baseline parameters and various aspect of ocular and systemic development during the observation period.…”
mentioning
confidence: 99%